X-ray tomography study on the structure of the granular random loose packing *Project supported by the Thirteenth Shanghai Jiao Tong University Students Innovation Practice Plan, China (Grant No. IPP13086), the National Natural Science Foundation of China (Grant Nos. 11175121, 11675110, and U1432111), and the Specialized Research Fund for the Doctoral Program of Higher Education of China (Grant No. 20110073120073). (August 2017) - Xing 邢, Yi 义; Qiu 邱, Yu-Peng 宇鹏; Wang 王, Zhi 智; Ye 叶, Jia-Chao 佳超; Li 李, Xiang-Ting 向亭
Abstract : Random loose packing is the minimum-density granular packing which can maintain mechanical stability. In this study, x-ray tomography is used to investigate the internal structure of an isotropically prepared random loose packing through a special apparatus to minimize the effect of gravity. It is found that the minimum packing density is around 0.587. The microscopic structural analysis of the packing is also carried out.